Landmarks of evolution of hip joint endoprosthesing. - A. Ye. Oleynyk (Medičnì Perspektivi)
The most important periods of history of hip joint replacement are considered in this work. Endoprosthesing is the replacement of pathologically changed joint with artificial one which is called the endoprosthesis. Special attention is paid to the creation and development of ideas, approach and principles of endoprosthesing as well as to materials and structures of implants. The period from the first attempt of joint replacement to the development of scientific foundation and creation of industry of modern endoprosthesing is overviewed. Together with the world practice the author also considered the history of endoprostesing in USSR and CIS countries. The approach to the solution of endoprosthesing problem in Ukraine is proposed. The essential scientific and practical achievements in the field of development of the native joint replacement are noted. Some modifications of hip endoprostheses and also of shoulder, ankle, first metatarsophalangeal joint and head of the radius are developed and manufactured. The work as for the improvement of the design of implants and elaboration of endoprostheses of other localizations is being performed. These investigations are performed in different directions and include the tasks of biomechanics of the locomotor system, development of new kinds of constructions, elaboration of new coatings and experimental investigation of the characteristics of implants.